2017
DOI: 10.1002/j.1681-4835.2017.tb00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of Human Competencies with Mobile Phone Technology and Business Strategies by Women‐LED SMEs in South Africa

Abstract: Women-led SMEs are faced with challenges that inhibit the performance of their businesses. By aligning their human competencies, mobile phone technology and the appropriate business strategy, they can steer their businesses to better performance. However, there is a scarcity of studies providing insight into how they can achieve this. Given the existence of the interplay between human competencies, mobile technology and business strategy, the perspective of alignment as Gestalts was adopted to determine the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
(69 reference statements)
2
12
0
Order By: Relevance
“…If you can store this information I can know, maybe I can refer that rule [if a dispute arises]. … Especially the health and safety rules are important as many workers come from villages [RMG_W5].We found evidence that MbUS‐based access to information not surprisingly empowers individuals, which complements prior research (Ajumobi & Kyobe, 2017; Garcia et al, 2014; Grindrod, 2016; Rashid et al, 2016; Ruiz‐Fernández et al, 2017). Our study found access to information for RMG's workers consisted of several empowering processes ‐ communication, reading and learning, employment regulations and access to health, and safety information.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…If you can store this information I can know, maybe I can refer that rule [if a dispute arises]. … Especially the health and safety rules are important as many workers come from villages [RMG_W5].We found evidence that MbUS‐based access to information not surprisingly empowers individuals, which complements prior research (Ajumobi & Kyobe, 2017; Garcia et al, 2014; Grindrod, 2016; Rashid et al, 2016; Ruiz‐Fernández et al, 2017). Our study found access to information for RMG's workers consisted of several empowering processes ‐ communication, reading and learning, employment regulations and access to health, and safety information.…”
Section: Resultssupporting
confidence: 76%
“…The interview participants explored several affordances of MbUS to RMGs. Our results are discussed in light of other MbUS studies (as e.g., Akter et al, 2017; Ajumobi & Kyobe, 2017; Garcia, Romero, Keyson, & Havinga, 2014; Grindrod, 2016; Rashid et al, 2016; Ruiz‐Fernández et al, 2017) in the following sections.…”
Section: Resultssupporting
confidence: 69%
“…Multiple studies have explored the advancements in mobile technologies and their use over the decade mainly from the perspective of businesswomen, patients, disabled, farmers, marginalized people, and fishermen (Ajumobi & Kyobe, 2017; Dasuki & Zamani, 2019; Iliya & Ononiwu, 2021; Misaki et al, 2018; Salia et al, 2011; Sam, 2015). Since the literature has mostly concentrated on the developing and the developed countries, the mobile phone usage behavior is underexplored in the Gulf countries (Alharthi & Islam, 2021; Zaidan, 2017), which lies in‐between the developing and the developed world as high‐income countries (Callen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Women entrepreneurs are primarily owners or managers or women responsible for making decisions of a business regardless of the sector or service or number of employees (Bradstätter, 1997; Ajumobi and Kyobe, 2017). The vision of closing the gender digital divide (GDD), i.e.…”
Section: Major Themes Emerging From the Literaturementioning
confidence: 99%
“…In their study on 70 women-led SMEs (firms or businesses that are owned, managed or partnered by women) in South Africa, Ajumobi and Kyobe (2017) attempted to understand how the alignment of mobile phone technologies, human competencies and business strategy (Muhanguzi and Kyobe, 2014; Kyobe et al , 2015) led to entrepreneurial success of women-led SMEs. Some of the major business strategies used by women-led SMEs in South Africa included market share and growth-oriented strategy, leveraging the use of IT trends strategy, customer-relationship and satisfaction-oriented strategy and conservative strategy (that involved attracting customers through cost cuts and word-of-mouth publicity).…”
Section: Major Themes Emerging From the Literaturementioning
confidence: 99%